Handbook of research on entrepreneurial leadership and competitive strategy in family business - Sáiz-Alvarez, José Manuel 1964-; Palma-Ruiz, Jesús Manuel 1978- (IGI Global, 2019)
"This book examines business strategies applied to family business that will boost efficiency, competitiveness, and optimal use of resources' allocation in companies competing internationally"...
Keywords: Family-owned business enterprises -- Case studies; Personnel management; Strategic planning; Strategisches Management; Entrepreneurship; Klein- und Mittelbetrieb